Effects of SARS CoV-2 mRNA Vaccines on Graves' Disease - Febriana, Gabriella Gita (Indonesian Journal of Life Sciences, 2023)
The development of SARS CoV-2 mRNA vaccines has been claimed as a breakthrough in the medical research field. Moreover, these vaccines have been proven to reduce SARS CoV-2 transmission. However, the administration of these vaccines also found to interfere with thyroid functions in some individuals, which include newly onset Graves’ disease in immunocompromised people and worsening condition in Graves’ disease patients. This article reviews cases on Graves’ disease following the administration of first and second dose of SARS CoV-2 mRNA vaccines between the year 2021 and 2022. Furthermore, the possible mechanisms of Graves’ disease development following mRNA vaccines administration are being discussed in this review article.